2018
DOI: 10.1186/s13046-018-0712-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient targeted tumor imaging and secreted endostatin gene delivery by anti-CD105 immunoliposomes

Abstract: BackgroundAnti-CD105 mAb-conjugated immunoliposomes, loaded with secreted mouse endostatin gene, were developed for targeted tumor imaging and antiangiogenic gene therapy.MethodsThe liposomes were investigated for size, zeta-potential, lipid content, antibody binding ability, and pcDNA loading capacity. The ability of immunoliposomes to target tumor-derived endothelial cells and perform gene transfer in vitro was measured and their basic biocompatibility was evaluated. A nude mouse/breast cancer xenograft mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
(46 reference statements)
1
14
0
1
Order By: Relevance
“…Previous studies showed that various carriers such as chitosan or liposome could enhance the solubility of quercetin and improve its bioactivity for treating tumor [12] and diabetes [13,14]. A drug delivery system is needed to improve the accumulation and bioavailability of quercetin in liver.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that various carriers such as chitosan or liposome could enhance the solubility of quercetin and improve its bioactivity for treating tumor [12] and diabetes [13,14]. A drug delivery system is needed to improve the accumulation and bioavailability of quercetin in liver.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al also developed CD105-conjugated targeted cationic microbubbles for antiangiogenesis gene therapy for breast cancer [198]. Similarly, endostatin loaded and CD105 antibody conjugated immunoliposomes were prepared for antiangiogenic and imaging therapy [199]. Gu et al also prepared CD44 antibody conjugated and anti-MDR1/P-gp short hairpin RNA complexed nanosystem for reversal of drug resistance.…”
Section: Breast Cancer Therapymentioning
confidence: 99%
“…To offer greater diagnostic-therapeutic precision it is necessary to look for further developments. Antibody formats, such as single-chain antibodies [15], diabodies, nanobodies and minibodies have now been labeled with positron emitters, allowing rapid imaging with high contrast [16].…”
Section: Introductionmentioning
confidence: 99%